Measuring serum estradiol and progesterone one day prior to frozen embryo transfer improves live birth rates - Alur-Gupta, Snigdha (Fertil Res Pract, 2020)
BACKGROUND: Given no consensus in the literature, this study sought to determine if a protocol of measuring serum estradiol and progesterone the day prior to frozen embryo transfer (FET) improves likelihood of pregnancy and livebirth. METHODS: This was a retrospective time-series study of women undergoing autologous vitrified-warmed blastocyst programmed FETs at an academic institution. Live birth rates were compared between a surveillance protocol, where serum estrogen and progesterone surveillance are performed the day prior to a programmed FET, and a standard protocol, whereby no hormonal lab evaluation is performed the day prior. RESULTS: Three hundred seventy-nine standard FET and 524 surveillance FET cycles were performed. Patients in the surveillance protocol were significantly more likely to achieve live birth (51% vs. 39%; aOR 1.6, 95%CI [1.2, 2.2]). Obese women were noted to be more likely to have lower progesterone hormone levels on surveillance labs (OR 3.2, 95%CI [2.0, 5.3]). However those whose hormonal medication dose was modified because of pre-transfer labs were as likely to achieve live birth as those whose dose was not modified (47% vs. 53%; aOR 0.8, 95%CI [0.6, 1.2]). CONCLUSIONS: Cycles with the surveillance protocol were more likely to result in live birth. Patients with low levels of pre-transfer hormones, such as obese patients, likely have lower pregnancy rates. It is possible that when these levels were corrected after measurement, pregnancy rates improved to match those whose levels were not low enough to warrant intervention.